Artists, territories and cultural policy: Recent dynamics in three Portuguese cities - Machado, A. F.; Costa, P. (Journal of Tourism and Cultural Change, 2024)
Contemporary economies are focused on issues anchored by place/territory, through public policies and market strategies. Municipal policies have a greater advantage in the cultural sector than other levels of governance (provinces/states, country) since cities have tools and instruments to shape the cultural economy to a local character and meet their specificities and local creative milieus. Having this in mind, this work seeks to analyse the relationship between artists and cultural spaces in three Portuguese cities: Lisbon, Porto and Évora. This paper aims to identify the relationship between artistic, cultural and creative agents with the place, mediated by the actions of these actors themselves, their networks as well as cultural policies Interview guides were prepared considering the specific context and art worlds of these cities. Around 60 people, including artists and creatives, representatives of groups/collectives and managers of cultural spaces, answered the questions in person or through online meetings using the available platforms. The main results show that the impacts are quite different between the cities. However, gentrification and real estate pressure represent significant challenges for the local artistic community. In all cities, the difficulty of raising funds for cultural activities is a recurring concern. Additionally, the relationship between public management and artists is often debated, with criticisms of centralization of power and lack of creative autonomy.